2020
DOI: 10.37939/jrmc.v24isupp-1.1443
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of HRCT-Thorax for pandemic COVID-19 pneumonia in Pakistan

Abstract: Background: In the scenario of, inadequate testing, the low sensitivity of the COVID-19-PCR test, limited availability of testing kits, and low detection rate, we aimed to investigate the usefulness of high-resolution computed tomography of chest (HRCT) for diagnosing pandemic coronavirus (COVID-19) pneumonia. Objective: To determine the diagnostic efficacy of HRCT thorax in Covid-19 pandemic pneumonia. Materials and Methods: This prospective, cross-sectional study was conducted in the Pulmonology–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In a local study by Qureshi et al, HRCT reported sensitivity and specificity of 97.41% and 80%, respectively, with a positive predictive value of 99.12% and a negative predictive value of 57.14%. Furthermore, they reported the diagnostic accuracy of HRCT for COVID-19 to be 96.69% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a local study by Qureshi et al, HRCT reported sensitivity and specificity of 97.41% and 80%, respectively, with a positive predictive value of 99.12% and a negative predictive value of 57.14%. Furthermore, they reported the diagnostic accuracy of HRCT for COVID-19 to be 96.69% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reduced sensitivity of RT PCR, many patients remain unidentified. This delays treatment and also contributes to the transmission of COVID-19 infection [8][9][10]. Computed tomography is technically not as demanding as RRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations